The Export Performance of Indonesia’s Palm Oil in International Market - Maria Ulfah; R. Hanung Ismono; Ktut Murniati (School of Business, Bogor Agricultural University (SB-IPB), 2019)
This study aims to analyze the performance of Indonesian exports to export destination countries in the international market. The subjects of this study are two Indonesian palm oil commodities: crude palm oil or CPO and processed palm oil or OPO (Other Palm Oil). There are four Indonesian palm oil markets in the international market, namely the Asian market, the European market, the African market, the American market, and the Australian market. The data used in this study is a time series from 1991 to 2016 and analyzed using the CMS (Constant Market Share) method. The CMS method explains the export growth performance in several components, which are the standard growth effect, the effect of product composition, the effect of market distribution, and the effect of competitiveness. The results showed that the performance of Indonesian CPO exports in the period 1991-2016 tended to decline compared to the growth of exports of all world products. Indonesian CPO is more competitive in the Asian market than the European market. The dynamics of Indonesian CPO exports in the African, American and Australian markets are quite good, but these three markets have not become the main destinations for Indonesian CPO exports. Indonesia's OPO export performance in the 1991-2016 period tended to increase compared to the growth in exports of all world products. Indonesian OPO in the Asian and African markets is more competitive than the European market. The dynamics of Indonesia's OPO exports on the American market and the Australian market are quite good, but these two markets have not become the main destinations for Indonesia's OPO market. Thus, Indonesia can maximize the performance of OPO exports when there is a rejection of Indonesian OPO in the international market.Keywords: CPO, constant market share (CMS), export, palm oil, performance